Duration of Heightened Ischemic Stroke Risk After Acute Myocardial Infarction. Issue 22 (20th November 2018) - Merkler, Alexander E.; Diaz, Ivan; Wu, Xian; Murthy, Santosh B.; Gialdini, Gino; Navi, Babak B.; Yaghi, Shadi; Weinsaft, Jonathan W.; Okin, Peter M.; Safford, Monika M.; Iadecola, Costantino; Kamel, Hooman
Abstract : Background: The duration of heightened stroke risk after acute myocardial infarction (MI) remains uncertain. Methods and Results: We performed a retrospective cohort study using claims between 2008 and 2015 from a nationally representative 5% sample of Medicare beneficiaries aged ≥66 years. Both acute MI and ischemic stroke were ascertained using previously validated International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD‐9‐CM ), diagnosis codes. To exclude periprocedural strokes from percutaneous coronary intervention, we did not count strokes occurring during an acute MI hospitalization. Patients were censored at the time of ischemic stroke, death, end of Medicare coverage, or September 30, 2015. We fit Cox regression models separately for the groups with and without acute MI to examine its association with ischemic stroke after adjustment for demographics, stroke risk factors, and Charlson comorbidities. We used the corresponding survival probabilities to compute the hazard ratio in each 4‐week interval after discharge. Confidence intervals were computed using the nonparametric bootstrap method. Among 1 746 476 eligible beneficiaries, 46 182 were hospitalized for acute MI and 80 466 for ischemic stroke. After adjustment for demographics, stroke risk factors, and Charlson comorbidities, the risk of ischemic stroke was highest in the first 4 weeks after discharge from the MI hospitalization (hazard ratio: 2.7; 95% confidence interval, 2.3–3.2), remained elevated during weeks 5 to 8 (hazard ratio: 2.0; 95% confidence interval, 1.6–2.4) and weeks 9 to 12 (hazard ratio: 1.6; 95% confidence interval, 1.3–2.0), and was no longer significantly elevated afterward. Conclusions: Acute MI is associated with an elevated risk of ischemic stroke that appears to extend beyond the 1‐month window that is currently considered the at‐risk period.